Integrated bioinformatics and network pharmacology analysis to reveal the therapeutic targets and potential molecular mechanism of Traditional Chinese Medicine Lianhua-Qingwen capsule on children's influenza - Lijuan Fang; Caiyan Li; Haimai Ding; Jinjin Tao (Phytomedicine Plus)
Background Influenza annually affects 5%-10% of adults and up to 20%-30% of children worldwide, with pediatric populations being more susceptible to severe complications and even mortality due to their immature immune systems. Traditional Chinese Medicine (TCM) demonstrates unique advantages in influenza treatment through multi-target mechanisms inhibiting viral replication and modulating host immunity. As a clinically prevalent TCM formulation for respiratory infections, the molecular mechanisms underlying Lianhua Qingwen Capsule's (LHQW) therapeutic effects against pediatric influenza remain elusive.Purpose and methods This study focuses on children and combines network pharmacology, molecular docking, and pediatric influenza target data to reveal the molecular mechanism of LHQW therapy for influenza virus infection, breaking through the limitations of adult influenza mechanism research. Through integrating childhood influenza targets with LHQW active ingredients, a ''disease drug'' interaction network was constructed, and a ''principal component-micro regulation'' synergistic model of herbal formulas was established, providing a digital research paradigm for analyzing the compatibility principles of herbal formulasResult Network pharmacology and molecular docking experiments have shown that LHQW mainly exerts therapeutic effects through the TNF and TLR4 signaling pathways. In vitro experiments have shown that LHQW has a significant inhibitory effect on the virus, with IC50 and TC50 values of 6.68 ± 1.03 μM and 9.97 ± 1.26 μM, respectively. In vivo experiments have confirmed that LHQW can improve the survival rate of mice, promote weight recovery, reduce viral titers, enhance antiviral antibody levels, and reduce lung index, inflammatory cytokine levels, and lung injury. Moreover, LHQW improves inflammation and oxidative stress by inhibiting the expression of TLR4 and MyD88, while reducing lung tissue cell apoptosis.Conclusion Notably, we pioneer in elucidating LHQW's dual-target mechanism that concurrently disrupts viral lifecycles and modulates host factors, thereby opening new avenues for developing antiviral therapeutics.